CALCULATION OF RESERVE LIFE REMAINING OF THE M5A DEPOSIT COAL REMOVAL MACHINE - Alin STĂNCIOIU (Fiabilitate şi Durabilitate)
The imposed conditions help us to determine according to the operation history of the machine, the number of cycles to which the metal construction was subjected and then the number of cycles to which theoretically the machine can still operate.